Enhancing patient safety by integrating ethical dimensions to Critical Incident Reporting Systems - Wehkamp, Kai; Kuhn, Eva; Petzina, Rainer; Buyx, Alena; Rogge, Annette (BMC Medical Ethics, 2021)
BACKGROUND: Critical Incident Reporting Systems (CIRS) provide a well-proven method to identify clinical risks in hospitals. All professions can report critical incidents anonymously, low-threshold, and without sanctions. Reported cases are processed to preventive measures that improve patient and staff safety. Clinical ethics consultations offer support for ethical conflicts but are dependent on the interaction with staff and management to be effective. The aim of this study was to investigate the rationale of integrating an ethical focus into CIRS. METHODS: A six-step approach combined the analysis of CIRS databases, potential cases, literature on clinical and organizational ethics, cases from ethics consultations, and experts' experience to construct a framework for CIRS cases with ethical relevance and map the categories with principles of biomedical ethics. RESULTS: Four main categories of critical incidents with ethical relevance were derived: (1) patient-related communication; (2) consent, autonomy, and patient interest; (3) conflicting economic and medical interests; (4) staff communication and corporate culture. Each category was refined with different subcategories and mapped with case examples and exemplary related ethical principles to demonstrate ethical relevance. CONCLUSION: The developed framework for CIRS cases with its ethical dimensions demonstrates the relevance of integrating ethics into the concept of risk-, quality-, and organizational management. It may also support clinical ethics consultations' presence and effectiveness. The proposed enhancement could contribute to hospitals' ethical infrastructure and may increase ethical behavior, patient safety, and employee satisfaction.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Categorization; CIRS; Ethics management; Healthcare; Quality management; Risk management